2020
DOI: 10.1021/acs.joc.0c02322
|View full text |Cite
|
Sign up to set email alerts
|

External Electric Fields Interrupt the Concerted Cope Rearrangement of Semibullvalene

Abstract: The topic of this paper is whether the mechanism of the degenerate Cope rearrangement of semibullvalene can be affected by the presence of electrostatic fields. Herein, we report that the shape of the energy surface, as demonstrated by an "interrupted" (stepwise) mechanism, is altered in the presence of a copper cation, Cu + . Natural bond-orbital and block-localized wave-function energy decomposition analyses suggest that orbital and electrostatic interactions play a major role in altering the shape of the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…2 The key to the understanding of global solvent effects, whether in the solid or liquid state, could lie in the impact of electric fields, a topic that has recently gained attention in the theoretical community. Semibullvalene became an intriguing model system for the study of both thermal 32 and tunneling 33 pathways of the Cope rearrangement. These studies suggest that even small electrostatic fields, e.g.…”
Section: ■ Heavy-atom Tunneling With Low Exothermicity: Oxepin/benzen...mentioning
confidence: 99%
“…2 The key to the understanding of global solvent effects, whether in the solid or liquid state, could lie in the impact of electric fields, a topic that has recently gained attention in the theoretical community. Semibullvalene became an intriguing model system for the study of both thermal 32 and tunneling 33 pathways of the Cope rearrangement. These studies suggest that even small electrostatic fields, e.g.…”
Section: ■ Heavy-atom Tunneling With Low Exothermicity: Oxepin/benzen...mentioning
confidence: 99%
“…This system has a similar double-well potential as PL, but it has the advantage of having been thoroughly studied not only theoretically but also experimentally in cryogenic matrices. 53,58–61 Previous SCT computations at the B3LYP/6-31G(d) level 60 gave k = 1.4 × 10 −3 s −1 below 40 K (Δ H ‡ = 19 kJ mol −1 ), while the experiments in cryogenic matrices produced rate constants of the order of 10 −4 s −1 , 58,59 depending on the matrix. This attests to the fortuitous error cancellation with B3LYP that provides accurate QT results only when compared to interacting environments (which tend to accelerate the reaction).…”
Section: Resultsmentioning
confidence: 99%
“…The influence of the EEF has similarities with the effect produced by individual atoms or even of the matrix experimentally and computationally observed on SBV and other molecules. 49,58,61,66,92,93 Small electrostatic effects at very short distance, along other effects, can perturb both the kinetics and the thermodynamics in such sensitive reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Electric fields have been regarded as the key player in enzymatic catalysis. For instance, Warshel and co-workers proposed that nature has taken advantage of pre-oriented intrinsic electric fields for electrostatic catalysis in enzymes, while Shaik and other research groups found that electric fields could act as a “smart reagent” in modulating the activity and selectivity of chemical reactions. In experiments, Boxer and co-workers have utilized vibrational Stark spectroscopy to quantify electric field strength at the active site of ketosteroid isomerase, which enabled them to correlate the electric field strength with reaction barriers in multiple ketosteroid isomerase variants. , Indeed, the role of local electric fields in enzyme catalysis has been regarded as “natural switches” to control the reactivity and selectivity of enzymes. …”
Section: Introductionmentioning
confidence: 95%